TOA localization for multipath and NLOS environment with virtual stations - Deliang Liu; Ying Wang; Peng He; You Zhai; Hongyun Wang (EURASIP Journal on Wireless Communications and Networking, 2017)
Abstract An effective geometrical method which can locate a source based on the time-of-arrival (TOA) measurements and the floor plan information is proposed in simple non-line-of-sight (NLOS) indoor environment where the multiple-bound scattering signal paths can be ignored. The novelty of our work resides in converting the NLOS problem into line-of-sight (LOS) problem based on the virtual stations (VSs), so that the localization algorithm for LOS conditions can be applied in simple NLOS conditions. The performance bound of the proposed method is also analyzed. Simulation results demonstrate the effectiveness of the proposed method.